2007
DOI: 10.1007/s11259-007-3505-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile of Erythromycin after Intramammary Administration in Lactating Dairy Cows with Specific Mastitis

Abstract: The pharmacokinetics of erythromycin was studied in five lactating dairy cows following single intramammary infusion of 300 mg erythromycin in each of two quarters per cow with specific mastitis. Levels of erythromycin in plasma and quarter milk samples were measured by agar plate diffusion assay using Micrococcus luteus (ATCC 9341) as the test organism. Erythromycin level in plasma reached a peak concentration value (C(max)) of 0.07 +/- 0.01 microg/ml at 30 min; thereafter, levels declined gradually to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Such crossover of drug to untreated quarters following intramammary administration has been observed previously in cattle for macrolide antibiotics (Bajwa et al 2007) and lincomycin (Milashki et al 1990). In a pharmacokinetic study of erythromycin in lactating cows, Bajwa et al (2007) found that following intramammary administration, the drug reached peak plasma concentrations at 30 min and was detected in milk of untreated quarters as early as 3 h. The crossover of drug residue to untreated quarters seems to be affected by the dose infused (Table 3). Generally, drug did not cross to any of 12 healthy or two latently infected (i.e.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Such crossover of drug to untreated quarters following intramammary administration has been observed previously in cattle for macrolide antibiotics (Bajwa et al 2007) and lincomycin (Milashki et al 1990). In a pharmacokinetic study of erythromycin in lactating cows, Bajwa et al (2007) found that following intramammary administration, the drug reached peak plasma concentrations at 30 min and was detected in milk of untreated quarters as early as 3 h. The crossover of drug residue to untreated quarters seems to be affected by the dose infused (Table 3). Generally, drug did not cross to any of 12 healthy or two latently infected (i.e.…”
Section: Discussionsupporting
confidence: 64%
“…Erythromycin, a low cost macrolide antibiotic, has proven to be very useful in veterinary medicine. The drug follows a rapid and good distribution in mammary gland after intramammary administration (Bajwa et al 2007) and possesses a marked in vitro activity against a variety of organisms isolated from mastitic udders of dairy cows (Getahun et al 2008). Even in vivo clinical trials of the drug have shown beneficial effects in the therapy of bovine mastitis (Shephard et al 2000;Bajwa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Whittem (1999) used a 2-compartment model for pirlimycin data in a study that employed population pharmacokinetics. Wuschko et al (1998) and Smith et al (2004) fitted 1-compartment models to milk concentrations of erythromycin 4267 CEPHAPIRIN PHARMACOKINETICS and ceftiofur, respectively, whereas Bajwa et al (2007) used noncompartmental modeling to study the pharmacokinetics of erythromycin. None of the previous studies investigated the effect of milking frequency or dosing interval on pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…use microbial inhibition tests as less expensive alternatives for detecting antimicrobial agents in milk (Moretain and Boisseau, 1989;Bajwa et al, 2007). However, nonspecific antimicrobial inhibitors in milk can affect microbial inhibition results (Andrew, 2001), and microbial inhibition tests cannot precisely distinguish CEPH and DAC.…”
Section: Discussionmentioning
confidence: 99%
“…Although beta-lactam antibiotics have widely been used for the treatment of staphylococcal mastitis, macrolides and lincosamides (ML) are the choice of antibiotics when betalactam resistance occurs [2,5,10]. Previous studies have demonstrated that resistance to beta-lactam antibiotics is common in staphylococci causing bovine mastitis in Turkey.…”
mentioning
confidence: 99%